Temperature‐Controlled High‐Speed AFM: Real‐Time Observation of Ripple Phase Transitions. Issue 44 (20th September 2016) - Takahashi, Hirohide; Miyagi, Atsushi; Redondo‐Morata, Lorena; Scheuring, Simon
Abstract : With nanometer lateral and Angstrom vertical resolution, atomic force microscopy (AFM) has contributed unique data improving the understanding of lipid bilayers. Lipid bilayers are found in several different temperature‐dependent states, termed phases; the main phases are solid and fluid phases. The transition temperature between solid and fluid phases is lipid composition specific. Under certain conditions some lipid bilayers adopt a so‐called ripple phase, a structure where solid and fluid phase domains alternate with constant periodicity. Because of its narrow regime of existence and heterogeneity ripple phase and its transition dynamics remain poorly understood. Here, a temperature control device to high‐speed atomic force microscopy (HS‐AFM) to observe dynamics of phase transition from ripple phase to fluid phase reversibly in real time is developed and integrated. Based on HS‐AFM imaging, the phase transition processes from ripple phase to fluid phase and from ripple phase to metastable ripple phase to fluid phase could be reversibly, phenomenologically, and quantitatively studied. The results here show phase transition hysteresis in fast cooling and heating processes, while both melting and condensation occur at 24.15 °C in quasi‐steady state situation. A second metastable ripple phase with larger periodicity is formed at the ripple phase to fluid phase transition when the buffer contains Ca 2+ . The presented temperature‐controlled HS‐AFM is a new unique experimental system to observe dynamics of temperature‐sensitive processes at the nanoscopic level. Abstract : Temperature‐controlled high‐speed atomic force microscopy (HS‐AFM) enables real‐time imaging while changing the environmental temperature. Real‐time imaging of 1, 2‐dimyristoyl‐ sn ‐glycero‐3‐phosphocholine lipid bilayers with temperature‐controlled HS‐AFM shows phase transitions (ripple to metastable ripple to fluid) while increasing temperature. Temperature‐controlled HS‐AFM is a powerful tool for real‐time analysis of temperature‐sensitive biological processes, such as lipid phase transition, dynamics of enzymatic reactions, and diffusion, to name a few.